International Students Destination Loyalty Behavior: Conceptual Framework for Emerging Destinations - Manzuma-Ndaaba, Ndanusa Mohammed; Harada, Yoshifumi; Romle, Abd Rahim; Shamsudin, Abdul Shukor (International Review of Management and Marketing, 2016)
The encroachment of marketing theories in to education services through up some research challenges resulted in different models. However, previous focuses were more on student’s satisfaction, leaving out retention which has been adjourned to save cost, energy and time than recruitment. Therefore, this study conceptualized an integrated frame work for loyalty study in international higher education from marketing perspective. The objective is to integrate variables applicable to situation of developing country sourcing international students from developing countries. The liberalization of education sector encouraged by globalization resulting from reduced government finances and economic gains attached to international education services gave rise to emerging education destinations. This study contributes to theory by proposing an integrated model for loyalty behavior in international education. Also contributes to practice by identifying variables that will encourage students to continue their study, re-enroll for next degree, recommend the country and speak well of the destination. Malaysia stands to gain from the prepositions and variables in this study. The study is limited by its very nature of being a conceptual study, thus empirical study is recommended. Keywords: Loyalty, Student Destination, Tertiary Education JEL Classifications: J10, M10